Biological Characterization and Evolutionary Dynamics of Pigeon Paramyxovirus Type 1 in China - Zhan, Tiansong; He, Dongchang; Lu, Xiaolong; Liao, Tianxing; Wang, Wenli; Chen, Qing; Liu, Xiaowen; Gu, Min; Wang, Xiaoquan; Hu, Shunlin; Liu, Xiufan (Frontiers in Veterinary Science, 2021)
Pigeon paramyxovirus type 1 (PPMV-1) is considered as an antigenic variant of Newcastle disease virus (NDV) which has an obvious host preference for pigeons and has caused significant economic losses to the global poultry industry. The evolutionary dynamics of PPMV-1 in China, however, are poorly understood. In this study, we characterized seven PPMV-1 isolates from diseased pigeons collected in Jiangsu, Anhui, and Henan provinces during 2020. Phylogenetic analysis revealed that seven isolates belonged to sub-genotype VI.2.1.1.2.2. Biological characterization indicated that seven isolates were mesogenic based on the mean death time (69.6-91.2 h) and intracerebral pathogenicity index (1.19-1.40) and had similar growth kinetics in chicken embryos and CEFs. Furthermore, the four representative viruses (AH/01/20/Pi, JS/06/20/Pi, HN/01/20/Pi and HN/02/20/Pi) could result in marked cytopathic effects (CPE) in CEFs and induced syncytium formation in Vero cells. Our Bayesian phylogenetic analysis showed that PPMV-1 might first emerge in East China in 1974 and East China had the highest genotypic diversity of PPMV-1. Besides, phylogeographic analysis indicated that East China and South China were probably the major epicenters of dissemination of PPMV-1 in China. Selection pressure analysis and amino acid substitutions analysis revealed that the viral replication complex (NP, P and L proteins) was likely related with the host preference of PPMV-1. Collectively, this study uncovered the epidemiology and evolutionary dynamics of PPMV-1 circulating in China, emphasizing the importance of strengthening the monitoring of PPMV-1 in East China and South China and providing significant clues for further studies on the molecular mechanism underlying host preference of PPMV-1.